Tillage and Nitrogen Placement Effects on Yields in a Short-Season Corn/Wheat/Double-Crop Soybean Rotation - D. W. Sweeney (Kansas Agricultural Experiment Station Research Reports, 2016)
(Abstract only. Link to: http://newprairiepress.org/kaesrr/vol1/iss4/2/) Article is nearly identical toTillage and Nitrogen Placement Effects on Yields in a Short-Season Corn/Wheat/Double-Crop Soybean Rotationpreviously published in Southeast Agricultural Research Center 2015. Overall in 2014, adding nitrogen (N) improved average wheat yields, but different N placement methods resulted in similar yields. Double-crop soybean yields were unaffected by tillage or the residual from N treatments that were applied to the previous wheat crop.
Keywords: Tillage; Nitrogen; Corn; Wheat; Soybean